2014
DOI: 10.1109/tns.2014.2356465
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Multichannel Low-Noise Front-End Readout ASIC Dedicated to CZT Detectors for PET Imaging

Abstract: In this paper, we present the design and preliminary results of a novel low-noise front-end readout application-specific integrated circuit (ASIC) for a PET imaging system whose objective is to achieve the following performances: the spatial resolution of mm , the detection efficiency of 15% and the time resolution of 1 ns. A cascode amplifier based on the PMOS input transistor is selected to realize the charge-sensitive amplifier (CSA) for the sake of good noise performances. The output of the CSA is split in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Therefore, we selected only the single-pixel photopeak events of pixelated CdZnTe detectors from the individual CdZnTe pixels. experiments for prototype conventional PET systems using CdZnTe detectors [14,15]. However, few studies have focused on simulating a PET insert system [16].…”
Section: Small-animal Pet Configurations and Monte Carlo Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we selected only the single-pixel photopeak events of pixelated CdZnTe detectors from the individual CdZnTe pixels. experiments for prototype conventional PET systems using CdZnTe detectors [14,15]. However, few studies have focused on simulating a PET insert system [16].…”
Section: Small-animal Pet Configurations and Monte Carlo Simulationsmentioning
confidence: 99%
“…Monte Carlo (MC) simulation offers a cost-effective and useful method to understand the imaging ability of a PET based on a pixelated CdZnTe detector [13]. Many studies have reported aspects of both simulations and experiments for prototype conventional PET systems using CdZnTe detectors [14,15]. However, few studies have focused on simulating a PET insert system [16].…”
Section: Introductionmentioning
confidence: 99%
“…An example of the development of improved electronics for small animal PET imaging with CdZnTe detectors is given in [218]. Similarly, [79] describes ASICs, also coupled to CdZnTe detector arrays, but for photon counting X-ray CT.…”
Section: Instrumentation Dedicated To Medical Applicationsmentioning
confidence: 99%
“…Gao and co-authors [218] describe a very low noise readout ASIC to achieve 1 mm 3 resolution, a detection efficiency of 15%, 1 ns time resolution for gating and better than 2% energy resolution (FWHM) for scatter rejection (Fig. 18).…”
Section: Instrumentation Dedicated To Medical Applicationsmentioning
confidence: 99%
“…A large number of studies on proton and electron irradiation damage fully proved that TJ solar cells exhibit an exceptional irradiation resistance during the entirety of various space missions. [3][4][5][6][7][8] However, the excessive photocurrent in bottom (Ge) cell than that in the top (GaInP) and middle (GaAs) cells implies higher thermalization loss. [9] The thermalization loss can be reduced by adding additional junctions to increase the range of solar spectrum.…”
Section: Introductionmentioning
confidence: 99%